DENDROCHRONOLOGICAL STUDY OF Brosimum utile (Kunth) Oken FROM TIMBIQUÍ, CAUCA, COLOMBIA - Parada, Claudia Milena; Polanco, Cesar Augusto; Tomazello, Mario (Floresta, 2021)
Brosimum utile (Kunth) Oken is a timber-yielding high-potential species with elevated rates of forest harvest at large-scale commercial transport in Colombia. In order to provide silvicultural management elements for natural forests, this study applied dendrochronological technique in a manner that promoted sustainable methods to manage the species. In this study, ten timber dicks using wood-sampling logs from Timbiquí-Cauca were used. The logs’ surfaces were observed and prepared, and their growth rings were marked. By developing cross-dating and x-ray densitometry value analysis, accomplished in ESALQ-USP, Brazil, the study established the chronologies; and as a direct consequence, it obtained a correlation of 0.692. Afterwards, the standard chronology was correlated with rainfalls in a 44-year series. The growth was modeled using the Von Bertalanffy equation, and the current annual increment (CAI) and mean annual increment (MAI) were calculated, whose results were classified into five age-categories, obtaining 6.336 and 5.683 mm.year-1 as final values, respectively.